2020
DOI: 10.5751/es-11666-250408
|View full text |Cite
|
Sign up to set email alerts
|

Gardener demographics, experience, and motivations drive differences in plant species richness and composition in urban gardens

Abstract: Urban agriculture has received considerable attention for its role in supporting biodiversity and ecosystem services, and health and well-being for growing urban populations. Urban gardens managed with agroecological practices and higher plant diversity support more biodiversity and may support higher crop production. Plant selection in gardens is a function of temperature and environmental conditions and also depends on gardener socio-demographic characteristics, motivations for gardening, and gardening exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 41 publications
(74 reference statements)
6
44
1
2
Order By: Relevance
“…From a horticultural perspective, we found that gardens have many different cultivated food and flower crops involved in urban food production. The common crops grown in these gardens (e.g., Solanum lycopersicum, Fragaria × ananassa, Cucurbita pepo, Beta vulgaris) supports other studies in community gardens elsewhere (Philpott et al 2020). Yet some interesting "novel" crops were also found, including Glycine max (soy bean) in one garden, and Perilla frutescens (shiso) in another garden.…”
Section: High Diversity Of Cultivated and Wild Growing Plant Species ...supporting
confidence: 84%
See 1 more Smart Citation
“…From a horticultural perspective, we found that gardens have many different cultivated food and flower crops involved in urban food production. The common crops grown in these gardens (e.g., Solanum lycopersicum, Fragaria × ananassa, Cucurbita pepo, Beta vulgaris) supports other studies in community gardens elsewhere (Philpott et al 2020). Yet some interesting "novel" crops were also found, including Glycine max (soy bean) in one garden, and Perilla frutescens (shiso) in another garden.…”
Section: High Diversity Of Cultivated and Wild Growing Plant Species ...supporting
confidence: 84%
“…For this reason, novel urban ecosystems such as community gardens designed for food production and ornamental purposes provide an interesting system to examine plant species diversity. In these agroecosystems, plant species assemble through gardeners' preferences (e.g., ornamental) and motivations to garden (e.g., food, nature connection) (Clarke and Jenerette 2015;Egerer et al 2019b;Philpott et al 2020), but also through both spontaneous and anthropogenic seed dispersal (von der Lippe and Kowarik 2009;Piana et al 2019). Moreover, the flora of gardens is particularly influenced by the interaction of people's activities like planting, weeding (including using herbicides), watering, soil cultivation and fertilizing (Kendal et al 2012;Padullés Cubino et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to gardening behavior, other potential underlying motivations or habits of respondents should also be considered. Interestingly, educational background may also affect motivations to garden, as a recent study found that participants with less formal education were more likely to garden for recreational and health reasons and spent twice as long gardening per week as those with more formal education [ 64 ]. This is important to consider within the context of our study because, while we did not include educational background in our final multivariate model, the majority of our sample population attended university, which may have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…In the few cross-sectional studies that have examined, this relationship differs from ours, as they targeted populations with disabilities [ 40 ], specific groups of gardeners [ 34 ], or did not examine depression risk per se but rather mental health or well-being more generally [ 36 , 66 ]. Finally, studies examining aspects of gardening behavior and migration history are diverse and include research on potential benefits of gardening for people with a migration history [ 42 , 80 ], attitudes towards gardening [ 79 ], effects of gardening intervention projects [ 42 , 53 ] and even species composition of gardens in relation to migration history [ 64 ]. To our knowledge, however, we are among the first studies that examined if migration history is associated with gardening behavior in a general urban population.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is organized as follows: "the case study section" presents the case study in Munich, while "the methods" conceptually outlines HFC and its association with PEFB as well as detailing the survey instrument. Main results are presented in "the results", which considers sociodemographic factors that can influence urban gardeners' gardening experiences and behaviours (Philpott et al 2020). In "the discussion", we discuss the findings with a special focus on analysing relationships between HFC dimensions identified.…”
Section: Research Objectives and Paper Outlinementioning
confidence: 99%